Os benefícios do exercício físico nos sintomas na doença de parkinson: uma revisão sistemática - Costa, Lívia Sophia Sampaio da (Brasil, 2025)
Parkinson's disease (PD) is a chronic, idiopathic and degenerative disease of the central nervous system, characterized by tremor, rigidity and bradykinesia, and affects the basal ganglia with loss of neurons in the nigrostriatal and cortical pathways, causing an absence of dopamine production, which interferes with the function of the motor system and interferes with cognitive functions, attention capacity, gait, balance and posture. The study aims to review and summarize studies on the practice of physical exercise in individuals diagnosed with Parkinson's disease. This is a systematic review whose relevant search occurred in the Pubmed, Scielo, CAPES, Google Scholar, Scopus and Lilacs databases, considering case studies, abstracts, systematic reviews published in the last 5 years (2018 to 2022), combining results from different sources, providing more valid and reliable evidence, carrying out the PICO strategy (Population/Patient; Intervention; Comparison/Control; Outcomes), with the eligibility criteria being studies that address the benefits of physical exercise practice. Regarding the results, 76 duplicate articles were excluded. 1,474 studies were selected for reading the titles and abstracts and, subsequently, 1,450 were excluded, because they did not meet the criteria of the PICO strategy. Finally, 23 articles were read in full, of which 12 were excluded. In the end, a total of 11 studies were selected in this review. It is possible to express that in this review, it is concluded that exercise has been promoted as a means of non-pharmacological treatment for patients with PD. Of the different interventions and exercises contextualized above, positive impacts were observed in different physical, neurological and motor aspects. However, it is necessary to carry out new studies, directed by physical education professionals with patients with PD.